2020
DOI: 10.3390/vaccines8030433
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticle Acts as a Potential Adjuvant for Influenza Split Vaccine without Inducing Inflammatory Responses

Abstract: Vaccination is a critical and reliable strategy for controlling the spread of influenza viruses in populations. Conventional seasonal split vaccines (SVs) for influenza evoke weaker immune responses than other types of vaccines, such as inactivated whole-virion vaccines, although SVs are highly safe compared to other types. Here, we assessed the potential of the lipid nanoparticle (LNP) we developed as an adjuvant for conventional influenza SV as an antigen in mice. The LNP did not induce the production of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Besides, the developing strategy of vaccines has still studied for other diseases. Shirai et al demonstrated that LNPs could act as an adjuvant for influenza vaccines [ 162 ]. This was confirmed through the results about the immune-stimulatory effects on dendritic cells in mice and the protection ability of LNPs encapsulating the conventional seasonal split vaccine (SV) in comparison with bare SVs and SVs combined Alum.…”
Section: Lipid-based Nanoparticles For Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the developing strategy of vaccines has still studied for other diseases. Shirai et al demonstrated that LNPs could act as an adjuvant for influenza vaccines [ 162 ]. This was confirmed through the results about the immune-stimulatory effects on dendritic cells in mice and the protection ability of LNPs encapsulating the conventional seasonal split vaccine (SV) in comparison with bare SVs and SVs combined Alum.…”
Section: Lipid-based Nanoparticles For Vaccinesmentioning
confidence: 99%
“…Alum induced a high inflammatory response, which is considered a limitation of traditional adjuvants. In contrary, LNPs were able to induce SV-specific immune responses without inflammation [ 162 ]. Swaminathan et al also assessed the adjuvant activity of LNPs alone and of LNPs incorporating the synthetic TLR9 agonist, IMO-2125 adjuvant, in a mouse model [ 163 ].…”
Section: Lipid-based Nanoparticles For Vaccinesmentioning
confidence: 99%
“…Indeed, some NPs such as VLPs, lipid NPs, and Au NPs may serve as costimulatory (adjuvant) agents. 146 148 Also, polymeric or self-assembling protein NPs could encapsulate and preserve antigens against early biodegradation and elimination. 24 , 149 Moreover, NPs would be targeted toward the immune cells for enhanced responses.…”
Section: Nanoparticles For Anti-coronavirus Therapeuticsmentioning
confidence: 99%
“…[47]. Excessive immune reaction to LNPs is not desirable because uncontrolled cytokine release can lead to life-threating conditions; however, carefully designed im-mune response activation can be used as an adjuvant in RNA-LNP-based vaccines [48,49]. Though using cationic lipids has disadvantages, as detailed above, the positive charge very efficiently entraps nucleic acids.…”
Section: Cationic Lnpsmentioning
confidence: 99%